1989
DOI: 10.1159/000132758
|View full text |Cite
|
Sign up to set email alerts
|

Linkage analysis of human chromosome 4: exclusion of autosomal dominant retinitis pigmentosa (ADRP) and detection of new linkage groups

Abstract: As part of our ongoing linkage studies of degenerative retinal diseases, we tested seven DNA markers and two classical genetic markers from chromosome 4 in two extended families with autosomal dominant retinitis pigmentosa (ADRP). Our goals were (1) to detect or exclude linkage of ADRP to markers spanning most of chromosome 4 and (2) to contribute useful new information regarding the linkage map of this chromosome. Our results exclude linkage of ADRP from more than 82% of chro mosome 4. We detected four new li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The identification of the first mutation causing RP in human left the scientific community perplexed. After having localized the gene on a short interval of the long arm of chromosome 3, a dominant mutation in the gene encoding for the rhodopsin, the visual pigment of rods, was identified [73][74][75]. Electroretinogram (ERG) measurements of affected members of this pedigree confirmed that RP progresses from an early abnormal rod response to a subsequent altered cone response.…”
Section: Rod-derived Cone Viability Factormentioning
confidence: 92%
“…The identification of the first mutation causing RP in human left the scientific community perplexed. After having localized the gene on a short interval of the long arm of chromosome 3, a dominant mutation in the gene encoding for the rhodopsin, the visual pigment of rods, was identified [73][74][75]. Electroretinogram (ERG) measurements of affected members of this pedigree confirmed that RP progresses from an early abnormal rod response to a subsequent altered cone response.…”
Section: Rod-derived Cone Viability Factormentioning
confidence: 92%
“…It was not until 1989, though, that linkage studies on a family with ADRP made it apparent that a candidate gene approach to the study of the RP family of diseases was warranted. Humphries and his collaborators, as recently reviewed in this series (Humphries et al, 1993) had been working on a large Irish pedigree with ADRP for some time Daiger et al, 1989) and found that the anonymous DNA marker D3S47 tightly segregated with the disease phenotype in this family . The lod score calculated for the coinheritance of D3S47 and the ADRP disease gene was 14.7, an exceedingly high value which gave strong evidence for the locus of the disease on the long arm of chromosome 3 (i.e.…”
Section: Opsin: Molecular Pathologymentioning
confidence: 97%